Predicted thermal acceptance in naturally ventilated office buildings with double skin façades under Brazilian climates. (September 2016) - Barbosa, Sabrina; Ip, Kenneth
Abstract: This study has predicted the annual thermal acceptance levels in naturally ventilated office buildings with double skin façade (DSF) under different Brazilian regional climates. It builds upon the outcomes of a comprehensive research programme on the study of generic thermal performance of naturally ventilated office buildings with DSF, which has identified and evaluated the key design parameters affecting the thermal behaviour of DSF through computational simulation models. Taking into account Brazil's bioclimatic zones characteristics, including the solar incidence and wind conditions, design configurations are adapted, optimized and embedded within computational models for analysis. Thermal acceptance levels of each region, using operative temperatures as the thermal comfort index, are illustrated. The highest levels of thermal acceptance, as high as 90%, are experienced in the south and southeast regions. Around 65% can be achieved in regions of centre-west, north-west and coastal areas, but only 20% in the arid region of the north-east. Significance of these thermal acceptance levels is discussed and comparisons to single skin façade (SSF) models highlight the benefits and constraints of the application of the DSF. The methodology and the results developed from this study enable initial assessment of application of DSF in naturally ventilated buildings under warm and hot climates. Highlights: Correct specification of design parameters is paramount in achieving good thermal acceptance. DSF simulation models optimised for each bioclimatic zone in Brazil are developed. Ventilation strategies with DSF in different regions of Brazil are identified. Three representative regional thermal acceptance levels are established.